Sustainable finance in the Islamic world: A comparative study of ESG reporting in Indonesia, Malaysia, and Brunei Darussalam - Adirestuty, Fitranty; Ratnasari, Ririn Tri; Firmansyah , Egi Arvian; Al Adawiyah, Rumaisah Azizah; Chazanah , Indah Nur; Yuliawati , Tia (al-Uqud : Journal of Islamic Economics, 2025)
This research examines the sustainability reporting procedures of three Islamic banks located in Indonesia, Malaysia, and Brunei Darussalam. The research methodology employs a comprehensive and dependable descriptive approach, utilising a content analysis framework grounded in established sustainable practices and prior studies. This led to an extensive examination of 302 elements, encompassing environmental, socioeconomic, governance, and sharia compliance dimensions. The findings indicate that all three Islamic banks exhibit a commendable level of transparency and are dedicated to adopting sustainable practices. This signifies substantial transparency regarding governance and minimal disclosure concerning sharia compliance, reflecting the ethical identity of the IBs. Bank Syariah Indonesia has the highest degree of disclosure among all sampled banks. This study examines ESG disclosure in Islamic banks and paves the way for future research to broaden its coverage by include more factors. This may result in a more thorough investigation and further insights in the domain. The study's conclusions and suggestions could substantially influence Islamic banks, regulators, and other stakeholders.